Nutrient utilisation, growth performance and blood metabolites in Murrah buffalo calves (Bubalus bubalis) divergently selected for residual feed intake. Issue 6 (1st November 2016) - Sharma, Vijay K.; Kundu, Shivlal S.; Prusty, Sonali; Datt, Chander; Kumar, Muneendra
ABSTRACT: The aim of this study was to evaluate differences in efficiency of feed utilisation between buffalo calves with low and high residual feed intake (RFI) by comparing feed intake, nutrient digestibility, growth traits and blood metabolites. Eighteen male Murrah buffalo calves (aged 4–6 months; 70 ± 1.0 kg body weight) were fed ad libitum with a total mixed ration for 120 d. Based on linear regression models involving dry matter intake (DMI), average daily gain (ADG) and mid-test metabolic body size, calves were assigned into low and high RFI groups. The RFI varied from −0.33 to +0.28 kg DM/d with an average RFI of −0.14 and 0.14 kg DM/d in low and high RFI calves, respectively. Calves had a mean DMI of 1.9 and 2.4 kg/d and an ADG of 0.5 and 0.6 kg/d in low and high RFI groups, respectively. Low RFI calves ate 19.0% less DM each day and required significantly less metabolisable energy for maintenance compared with high RFI calves (12.5 vs. 16.7 MJ/d). Nutrient digestibility and nitrogen balance did not differ among low and high RFI calves. In more efficient animals (low RFI calves) higher ( p <  0.05) plasma level of growth hormone, insulin-like growth factor-1 (IGF-1), triiodothyronine (T3 ) and lower concentration of thyroxin hormone were detected. No significant differences in levels of insulin, hydroxyproline, plasma and urine creatinine, total protein and albumin between high and low RFI groups were found. Blood metabolites showed significant ( p  < 0.05) differences at initial and final stages of study in both groups. At final stage of study, RFI showed negative correlations with growth hormone, IGF-1, T3, urine creatinine and albumin. Low RFI buffalo calves are more efficient in feed utilisation and the differences in blood metabolites are probably due to differences in feed intake and body metabolism.